maths

posted by .

If alpha and beta are the roots of the equation 2x^2+ 4x + 1 = , find the values of log2alpha + log2beta

  • maths -

    If 2x²+4x+1 = 0
    Then: x = (-2±√2)/2

    let α = (-2+√2)/2
    let β = (-2-√2)/2

    log_2(α) + log_2(β)
    = log_2(αβ)
    = log_2((-2+√2)(-2-√2)/4)
    = log_2(1/2)
    = -1

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. maths

    Given that the roots of 2x^2-4x+5 are alpha and beta,find the value of ... (i)alpha^3beta^3 (ii)(alpha-beta)^2
  2. maths

    if alpha and beta are the zeros of the polynomial 2x^2-4x+5 then find the values of (i)alpha^2+beta^2 (ii)1/alpha^2+1/beta^2 (iii)(r)alpha/beta+(r)beta/alpha (iv)alpha^-1+beta^-1
  3. trig

    evaluate the following in exact form, where the angeles alpha and beta satisfy the conditions: sin alpha=4/5 for pi/2 < alpha < pi tan beta=7/24 for pie < beta < 3pi/2 answer choices A. sin(beta+alpha) B. tan(beta-alpha) …
  4. Math ( Polynomial )

    This time three questions - 1. If (x^2 - 1 ) is a factor of polynomial ax^4 + bx^3 + cx^2 + dx + e, show that a + c + e = b + d = 0. 2. Let R1 and R2 be the remainders when polynomials x^3 + 2x^2 - 5ax - 7 and x^ 3 + ax^2 - 12 x + …
  5. Math ( Polynomial )

    This time three questions - 1. If (x^2 - 1 ) is a factor of polynomial ax^4 + bx^3 + cx^2 + dx + e, show that a + c + e = b + d = 0. 2. Let R1 and R2 be the remainders when polynomials x^3 + 2x^2 - 5ax - 7 and x^ 3 + ax^2 - 12 x + …
  6. Math

    If alpha and beta are the zeros of the polynomial ax^2 + bx + c then evaluateA. (alpha)^2 / beta + (beta)^2 / alpha B. alpha^2 .beta + alpha.beta^2 C. 1/(alpha)^4 + 1/(beta)^4. Please work the complete solution.
  7. maths

    If alpha beta are the roots of a^2 +bx + c = 0. find the values of (beta/alpha^2)+ (alpha/beta^2)
  8. maths

    If alpha and beta are the zeros of the polynomial p(x)=x^2+x+1 then find the value of 1÷alpha+1÷beta 2)alpha^2+beta^2
  9. Maths

    If The Roots Of The Equation X^2- bx+c are square root of alpha and square root of beta .show that alpa + beta = b^2- 2c and (alpha)^2 + (beta)^2 = (b^2 -2c - sqrt of 2c)(b^2 - 2c + sqrt of 2c)
  10. Math

    If alpha, beta are the zeroes of x2-2x+3, find a quadratic equation whose roots are (alpha-1)(beta+1), (beta-1)(beta+1)

More Similar Questions